Teacher’s morphological awareness and errors in teaching English - Sukarton; Dewanti, Ratna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Morphology is the study of words and their structure, focusing on the relationships between morphemes. This study aims to examine teachers’ morphological awareness and errors in teaching English. A qualitative content analysis method was employed, with one English teacher as the participant, selected based on their extensive teaching content on YouTube. Observation sheets and criterion- referenced assessment (CRA) were used as data collection techniques. The findings indicate that the teacher's morphological awareness score is 71.42%, classifying them as